Resistance and renewal: health sector reform and Cambodia's national tuberculosis programme - Peter S Hill; Mao Tan Eang
Following the destruction of Cambodia's health infrastructure during the Khmer Rouge period (1975-1979) and the subsequent decade of United Nations sanctions, international development assistance has focused on reconstructing the country's health system. The recognition of Cambodia's heavy burden of tuberculosis (TB) and the lapse of TB control strategies during the transition to democracy prompted the national tuberculosis programme's relaunch in the mid-1990s as WHO-backed health sector reforms were introduced. This paper examines the conflicts that arose between health reforms and TB control programmes due to their different operating paradigms. It also discusses how these tensions were resolved during introduction of the DOTS strategy for TB treatment.